Failure analysis of screw shaft in screw compressor. (July 2021) - Wang, M.S.; Jia, X.D.; Lv, W.Y.; Sun, W.H.; Bai, F.X.; Guo, H.
Highlights: The failure analysis of screw shaft has been investigated. The failure mechanism for the failed screw shaft was multisource fatigue. The insufficient fatigue performance was due to the absence of surface hardening. Abstract: This paper analyses the root causes of screw shaft failure in screw compressors. The failure mechanism was studied by visual inspection, macro- and microfractography, chemical characterization, and mechanical property analysis. The results reveal that the main reason for the failure was multisource fatigue due to the lack of surface quenching at the fracture position of the shaft root. To prevent similar failures, better control of surface quenching is strongly recommended.